Fracture toughness of carbon fiber/polyether ether ketone composites manufactured by autoclave and laser‐assisted automated tape placement. Issue 11 (11th November 2014) - Ray, Dipa; Comer, Anthony J.; Lyons, John; Obande, Winifred; Jones, David; Higgins, Ronan M. O.; McCarthy, Michael A.
ABSTRACT A comparative study is presented on the fracture toughness of carbon fiber/PEEK composites manufactured by autoclave and laser‐assisted automated tape placement (LATP). Formation of a good inter‐laminar bond is always a concern in ATP due to the short time available for intimate contact development and polymer healing, yet our double cantilever beam (DCB) tests reveal 60–80% higher Mode I fracture toughness for the LATP processed specimens than for the autoclave processed specimens. This magnitude of difference was unexpected, so specimens were further examined via differential scanning calorimetry, dynamic mechanical analysis, nano‐indentation, and scanning electron microscopy. The results indicate that the LATP process has been very effective in heating and consolidating the surface of plies, creating an excellent bond. However, it has been less effective in processing the interior of plies, where a low crystallinity and poor fiber–matrix bonding are evident. The higher fracture toughness of the LATP processed specimens is also not solely due to a better bond, but is partially due to significant plastic deformation in the interior of plies during the DCB test. The findings indicate there is still considerable scope for optimizing the laser‐assisted ATP process, before the optimum balance between strength and toughness is achieved at favorable lay‐down speeds. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41643.